Applicant Desirability Influences Reactions to Discovered Résumé Embellishments. (7th February 2013) - Kuhn, Kristine M.; Johnson, Timothy R.; Miller, Douglas
<x xml:space="preserve">Abstract</x> This study investigates responses to a discovered résumé embellishment as a function of initial impressions of the applicant. In Study 1, managers and recruiters rated the extent to which a discrepancy uncovered by a background check would lower their opinion of an applicant, using a between‐subjects design crossing the applicant's apparent desirability and type of embellishment. In Study 2, business students completed a simulated hiring task in which they first evaluated applicants based on their résumés, then read background reports, and subsequently made a final evaluation. Results indicate interactive effects of an applicant's apparent desirability, type of deception revealed, and response dimension. The discovery of a minor embellishment has little effect on evaluations of favored applicants, but negatively impacts less desirable applicants.